Pengaruh Aspek-Aspek Demokrasi Indonesia Terhadap Pertumbuhan Ekonomi di Indonesia Periode 2016-2020 - Sabardin; Muhammad Ghafur Wibowo (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
This research aims to find out how aspects of democracy presented through civil liberties, political rights, and democratic institutions influence Indonesia's economic growth from 2016 to 2020. The Central Statistics Agency (BPS) provided the data and researchers used secondary data for this research from 2016 to 2022. The random effect model (REM) is the model selection test most commonly found in this research approach, which uses panel data regression analysis tools. It was found that variables related to democratic institutions positively and significantly influence economic growth. However, civil liberties and political rights did not affect Indonesia's economic growth from 2016 to 2020.